Forest and Land Tenure Conflict Resolution and Mechanism in Indonesia - CGIAR Research Program on Policies, Institutions, and Markets (2017)
ICRAF, together with NGO partners, developed a tool to resolve forest land tenure conflict in Indonesia, which the Ministry of Environment and Forestry (MoEF) through MoEF Regulation No. 84/2015 endorsed and adopted as training curricula and syllabus for forest managers (Human Resources Training and Education of MoEF No. 34/2014 and 94/2016).